Characterization of primary rat nasal epithelial cultures in CFTR knockout rats as a model for CF sinus disease. (3rd August 2017) - Tipirneni, Kiranya E.; Cho, Do‐Yeon; Skinner, Daniel F.; Zhang, Shaoyan; Mackey, Calvin; Lim, Dong‐Jin; Woodworth, Bradford A.
Abstract : Objective: The objectives of the current experiments were to develop and characterize primary rat nasal epithelial cultures and evaluate their usefulness as a model of cystic fibrosis (CF) sinonasal transepithelial transport and CF transmembrane conductance regulator (CFTR) function. Study Design: Laboratory in vitro and animal studies. Methods: CFTR +/+ and CFTR −/− rat nasal septal epithelia (RNSE) were cultured on semipermeable supports at an air–liquid interface to confluence and full differentiation. Monolayers were mounted in Ussing chambers for pharmacologic manipulation of ion transport and compared to similar filters containing murine (MNSE) and human (HSNE) epithelia. Histology and scanning electron microscopy (SEM) were completed. Real‐time polymerase chain reaction of CFTR +/+ RNSE, MNSE, and HSNE was performed to evaluate relative CFTR gene expression. Results: Forskolin‐stimulated anion transport (ΔIsc in μA/cm 2 ) was significantly greater in epithelia derived from CFTR +/+ when compared to CFTR −/− animals (100.9 ± 3.7 vs. 10.5 ± 0.9; P < 0.0001). Amiloride‐sensitive ISC was equivalent (−42.3 ± 2.8 vs. −46.1 ± 2.3; P = 0.524). No inhibition of CFTR‐mediated chloride (Cl − ) secretion was exhibited in CFTR −/− epithelia with the addition of the specific CFTR inhibitor, CFTRInh ‐172. However, calcium‐activated Cl − secretion (UTP) was significantly increased in CFTR −/− RNSE (CFTR −/− −106.8 ± 1.6 vs. CFTR +/+ −32.2 ± 3.1; P < 0.0001). All responses were larger in RNSE when compared to CFTR +/+ and CFTR −/− (or F508del/F508del) murine and human cells ( P < 0.0001). Scanning electron microscopy demonstrated 80% to 90% ciliation in all RNSE cultures. There was no evidence of infection in CFTR −/− rats at 4 months. CFTR expression was similar among species. Conclusion: The successful development of the CFTR −/− rat enables improved evaluation of CF sinus disease based on characteristic abnormalities of ion transport. Level of Evidence: NA. Laryngoscope, 127:E384–E391, 2017